An improved risk-benefit collaborative grey target decision model and its application in the decision making of load adjustment schemes. (1st August 2018) - Li, Rongbo; Jiang, Zhiqiang; Ji, Changming; Li, Anqiang; Yu, Shan
Abstract: Power generation plan formulated based on the forecasted runoff is an important basis for the actual operation of hydropower station. However, due to the forecast error, the load adjustment is necessary in the actual operation, and how to find out the most satisfactory load adjustment scheme from the scheme set is an important topic. So, in order to comprehensively reflect the risk and benefit state of hydropower station operation, a risk-benefit collaborative evaluating indicator system of load adjustment scheme is established firstly in this paper, and aim at the strong subjectivity of present evaluation methods, an improved grey target decision model based on moment estimation method is proposed, and the combinatorial weight integration technology and the Mahalanobis distance are coupled in this model. Taking the cascade hydropower stations of Yalong River in China as an instance, six schemes are evaluated by the proposed model, and the results are compared and analyzed with another six evaluation models. Results show that the proposed model can effectively coordinate different weighting methods and overcome the shortcomings of traditional grey target decision model about the insufficient consideration on the importance and correlation of evaluating indicators, and it has a good value of popularization and application. Highlights: Risk-benefit collaborative evaluating indicator system is established in this paper. An improved grey target decision model based on moment estimation method is proposed. The proposed model can effectively coordinate different weighting methods. Combinatorial weight technology and Mahalanobis distance are coupled in this model. Correlation and importance of indicators can be both considered in this model.